VIBROACOUSTIC DIAGNOSING OF DISTURBANCES IN THE CAR IGNITION SYSTEM BY AMPLITUDE ESTIMATES - Piotr CZECH; Grzegorz WOJNAR; Piotr FOLĘGA (Scientific Journal of Silesian University of Technology. Series Transport)
An important issue in vibroacoustic examination of engines is a correct interpretation of complex measured signals by applying property methods of their processing. The main tasks in diagnostics include: separation of a useful vibroacoustic signal and selection of characteristic, damage-sensitive features of the processed signal. The paper presents an attempt of detecting disturbances in the ignition system by measuring vibrations and noise. The object of the tests was a four-cylinder engine of a Volkswagen Polo car with swept capacity 1,0 dm3, adjusted to alternative power supply with the use of LPG gas fuel